2008
DOI: 10.1111/j.1365-2141.2008.07026.x
|View full text |Cite
|
Sign up to set email alerts
|

Strategic use of an adenoviral vector for rapid and efficient ex vivo‐generation of cytomegalovirus pp65‐reactive cytolytic and helper T cells

Abstract: +T cells. This implies that sufficient number of pp65-specific cytolytic and helper T cells for adoptive transfer may be obtained in only 2 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…We have previously shown that a population of CMV pp65 495–503 -specific T cells can be significantly expanded if T cells from CMV-seropositive, HLA-A2-positive blood donors are stimulated by Ad5(pp65)-transduced autologous DCs [16], [22]. However, large amounts of viral vector need to be used to obtain efficient transduction of DCs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that a population of CMV pp65 495–503 -specific T cells can be significantly expanded if T cells from CMV-seropositive, HLA-A2-positive blood donors are stimulated by Ad5(pp65)-transduced autologous DCs [16], [22]. However, large amounts of viral vector need to be used to obtain efficient transduction of DCs.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore constructed a non-modified Ad5(pp65) and a double-modified Ad5PTDf35(pp65), which both express the full-length CMV pp65 transgene. We transduced monocytes with Ad5(pp65) or Ad5PTDf35(pp65) at a relatively low dosage (100 evg/cell), differentiated them into DCs [16], [22] and used them to stimulate and expand autologous pp65-specific T cells. The Ad5PTDf35(pp65)-transduced DC stimulation increased the pp65 495–503 -reactive T cells population for all donors, approximately 50–100 fold, while Ad5(pp65)-transduced DC stimulation only increased the pp65 495–503 -reactive T cell population 2–8 fold (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Monocytes are precursors of dendritic cells and as such, highly interesting as cancer vaccines after being modified to express tumor-associated antigens, often in the form of an adenoviral vector carrying the transgene coding for the tumor-associated antigen. For example, efficient adenoviral transduction of monocytes is highly warranted for ex vivo generation of T cells against specific antigens [35]. Such T cells could then be used for adoptive transfer to cancer patients.…”
Section: Discussionmentioning
confidence: 99%